A Review on the Process-Structure-Performance of Lanthanum Strontium Cobalt Ferrite Oxide for Solid Oxide Fuel Cells Cathodes - Muhammed Ali Shaikh Abdul Kader Abdul Hameed; Muchtar, Andanastuti; Raharjo, Jarot; Khaerudini, Deni Shidqi (International Journal of Integrated Engineering, 2022)
Perovskite-structured La1-xSrxCo1-yFeyO3-? (LSCF) is a promising mixed ionic/electronic-conducting material that exhibits excellent electro-catalytic activity toward oxygen reduction and oxygen evolution reactions. LSCF offers potential applications in many processes, such as electrodes for solid oxide fuel cells (SOFCs), oxygen sensors, and dense membrane for oxygen separation and thus have been studied extensively in various fields. However, its physical and electrochemical properties are substantially influenced by dopant concentration, dopant type and processing conditions (synthesis methods, composite cathode effect, fabrication conditions, and chromium poisoning). Understanding and correlating the effect of LSCF composition, its synthesis methods, fabrication conditions, and its parameters are essential to enhance the performance of LSCF cathode for high- to- intermediate temperature SOFC applications. This review emphasizes the importance of enhancing the performance of LSCF cathode by optimizing the influential factors to facilitate and expedite research and development efforts for SOFC commercialization in the near future. Various synthesis and fabrication methods used to prepare and fabricate LSCF and LSCF-based composite cathodes are discussed in detail. Moreover, their pros and cons in optimizing the microstructure of LSCF cathodes are highlighted. Finally, the strategies to improve the long-term microstructural stability and electrochemical performances of the LSCF cathode are discussed.